Childcare leave: A right of children and parents - Pautassi, Laura Cecilia (2011)
Undeniably children need care from the moment of birth. They need feeding, health care, early stimulation, love and everything else that is part of full development. In Latin America and the Caribbean, care is traditionally provided at home, almost always by the mother. Sometimes she has help from the father, another family member or the community. She may have access to some form of public service or buy market services.